Combination of Botulinum Toxin and minocycline Ameliorates Neuropathic Pain Through Antioxidant Stress and Anti-Inflammation via Promoting SIRT1 Pathway - Yu, Zhi; Liu, Jiayu; Sun, Le; Wang, Yusheng; Meng, Hongmei (Frontiers in Pharmacology, 2021)
Neuropathic pain (NP) is one of the intractable complications of spinal cord injury(SCI) with poor prognosis and seriously affects the patients’ quality of life. Thus, we seek to determine the treatment effect and mechanism of multimodal therapies in a rat model of SCI-induced NP by combining treatment with the anti-inflammatory agent minocycline(MC) and botulinum toxin(BoNT). As a result, the combined utilization alleviated SCI-induced NP and reduced apoptosis, inflammation and oxidative stress of SCI by activating SIRT1 and dampening pAKT, P53 and p-NF-KB. Here, BoNT with the concentration of 0.1 nm and MC with the concentration of 20 uM were selected for the experiment in the primary microglia and astrocytes treated with LPS. It was found that the combination of BoNT and MC obviously inhibits the inflammatory response and oxidative stress of glial cells, and notably activates SIRT1 and restrains pAKT, P53 and p-NF-KB. Therefore, in the treatment of SCI-induced NP, combination of BoNT and MC markedly improves the therapeutic effect of NP by promoting the SIRT1 expression, thereby inactivating NK-KB, P53 and PI3K/AKT signaling pathway, inhibiting inflammation and oxidative stress as well as relieving SCI-induced NP.